2013
DOI: 10.1055/s-0033-1361176
|View full text |Cite
|
Sign up to set email alerts
|

CoQ10 and L-Carnitine Attenuate the Effect of High LDL and Oxidized LDL on Spermatogenesis in Male Rats

Abstract: Overall, pretreatment with coenzyme Q10 and L-Carnitine attenuated the destructive effects of high LDL and oxidized LDL levels on spermatogenesis parameters in male rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 1 publication
2
18
0
Order By: Relevance
“…22 Both sperm progressive motility and total motility were significantly higher in infertile patients after 3 months of antioxidant treatment. Our findings are consistent with previous studies which demonstrated higher sperm motility in patients with idiopathic infertility following vitamin C, 23 vitamin E, 3,18,20 zinc, 10,18,24 selenium, 3,18 and coenzyme Q10 8,18,25 administration. A recent study has compared the effect of L-carnitine vs a combination of zinc, vitamin E, selenium, coenzyme Q10, glutathione, and L-carnitine and reported improvement in all seminal fluid measures after 3 months of combined treatment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…22 Both sperm progressive motility and total motility were significantly higher in infertile patients after 3 months of antioxidant treatment. Our findings are consistent with previous studies which demonstrated higher sperm motility in patients with idiopathic infertility following vitamin C, 23 vitamin E, 3,18,20 zinc, 10,18,24 selenium, 3,18 and coenzyme Q10 8,18,25 administration. A recent study has compared the effect of L-carnitine vs a combination of zinc, vitamin E, selenium, coenzyme Q10, glutathione, and L-carnitine and reported improvement in all seminal fluid measures after 3 months of combined treatment.…”
Section: Discussionsupporting
confidence: 93%
“…However, during pathological conditions, when generation of ROS is exceeded, the balance between free radical production and the protective antioxidant defence system shifted to the increase in free radicalmediated oxidative stress. 8 Moreover, many studies have revealed that the antioxidant capacity of seminal fluid is suppressed in infertile men in comparison with fertile men. 6,9 Based on the integral role of oxidative stress in the pathogenesis of male infertility, treatment strategies that target the reduction of seminal oxidative stress have become a probable therapeutic window to improve reproduction potential and pregnancy rates.…”
Section: Introductionmentioning
confidence: 99%
“…Coenzyme Q10 (CoQ10), also termed as ubiquinone, is a respiratory chain component and acts as an antioxidant molecule. It is present in the human seminal fluid where it is involved in several antioxidant, mitochondrial bioenergetics and metabolic processes [14]. CoQ10 deficiency can lead to sperm damage, lower sperm motility and sperm count.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress has been implicated in the development of many diseases, such as cancer, diabetes, cardiovascular disease, rheumatoid arthritis, liver disease, AIDS (acquired immune deficiency syndrome), Parkinson disease, and motor neuron disease [ 4 ]. Reactive oxygen species (ROS) levels have been also linked to male infertility, and studies have reported higher levels of ROS and suppressed antioxidant capacity in the semen of infertile men in comparison to their fertile counterparts [ 5 6 7 ].…”
Section: Introductionmentioning
confidence: 99%